PELATIHAN PENGELASAN SMAW UNTUK SISWA JURUSAN TKRO SMK MANDIRI CIREBON - Leo Van Gunawan; Muhammad Ghozali; Mohammad Amat; Sukroni Sukroni; Nota S (Jurnal Pengabdian kepada Masyarakat (NADIMAS), 2023)
Alumni from study program of TKRO SMK Mandiri Cirebon are the most be at work in the industry. However, from several alumni working in the industry, there are some students working not according to their field. They are placed at manufacturing and welding. This community service activity provides SMAW training to student in the study program TKRO SMK Mandiri Cirebon as a provision for work or entrepreneurship. SMAW is the most commonly used welding in Indonesia. This training was carried out using the pre-experimental method type one group pretest-posttest design. The training activity begins with giving a pretest, theory learning, practice and closing with a posttest. Analysis value of pretest and posttest results was carried out using the Gain test formula. The results of value analysis get average N-Gain 0.414226. Based on N-Gain criteria, the value of 0.414226 is included in medium category. It can be concluded that the effectiveness of this training activity has a medium impact to increasing knowledge and skill students in SMAW Welding.